SIFAT SO’Z TURKUMINI O’RGANISH BILAN BOG’LIQ HOLDA SO’Z BIRIKMASI VA GAP TUZISHGA O’RGATISH USULLARI - Jono’zoqova Sevdora Baxtiyor qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article describes the methods of teaching primary school students to learn word combinations and sentence formation in secondary schools. Exercises from school textbooks are also presented and explained.